Ethical issues in exploiting and killing fish: understanding animal rights in Islam - Rahman, Mohammad Mustafizur (2016)
Fish is extremely important for human nutrition. Fish like many other animals face cruelty by human throughout the ages. Human show cruelty to fish during explointing, culturing, killing, experimentation and even in the name of sports or amusement. Presently, overexploitation of marine fishes is a serious problem worldwide. Overall, 53% of the world’s commercial fish stocks are currently reported as fully exploited and 32% are overexploited. More than 50% of of total fish production is now raised in aquafarms where fish spend their entire lives in culture systems where many suffer from parasitic infections, diseases, and debilitating injuries. Every year, millions of fish are caught in nets and on hooks. Some are destined for human consumption, many are tortured just for sport. Fishes are also regularly used in laboratories for biology lessons and curiosity-driven experimentation. Many of them are killed by unethical ways. According to Islam, although humankind is a superior creation of Allah (God), they do not have the right to treat animals as they would so dictate. Allah gaves human beings the role of steward –caliph–on earth. This role gives the human being responsibility to look after animals, to protect them, and not to abuse or threaten them. To Islam, Allah created the universe in perfect balance. According to Islam, human should not disturb the perfect balance universe created by Allah. Islam also prescribes a set of rules to reduce the pain and distress of animals during killing/ slaughtering of animal including fish. Human are not permitted to kill animals just for sports or amusements. Islam teaches that on the Day of Judgment all human will be questioned how animals were used in their daily life. Islam also guides humankind to treat animals with the utmost kindness and compassion.